2017
DOI: 10.1590/0100-29452017181
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Physical and Chemical Characteristics in Pequi Fruits

Abstract: The aim of this study was to estimate the effects of populations and mother trees over some characteristics on pequi (Caryocar brasiliense Camb.) fruits as well as their repeatability coefficient. Data came from two populations with 15 mother trees each, covering three years. The following physical and chemical characteristics were evaluated: total fruit weight; external mesocarp weight; number of putamens per fruit; total weight of putamens; total and average pulp weight; and proportion of the weight of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, this does not imply that the genetic variability for such a characteristic is also low, since such contribution to divergence is relative to the other characteristics. Proof of this is the significance of the mother trees effect within populations for such characteristics (Table 1), as well as the 51% estimate found for the repeatability of this characteristic in these same mother trees and years (Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…However, this does not imply that the genetic variability for such a characteristic is also low, since such contribution to divergence is relative to the other characteristics. Proof of this is the significance of the mother trees effect within populations for such characteristics (Table 1), as well as the 51% estimate found for the repeatability of this characteristic in these same mother trees and years (Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…The preponderance of genetic variation within populations in relation to variation between them is observed in several tree species for different phenotypic characteristics (Fernandes, 2008;Silva et al, 2012;Costa et al, 2016;Soares et al, 2017). These observations are also confirmed by studies carried out with the pequi tree in regions of northern Minas Gerais, where it was found that divergences among populations or between groups of populations for this species are relatively low (Melo Júnior et al, 2004;Fernandes, 2008).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations